Indonesian-Timor Leste Western Demarcation Line Dispute Settlement on Unresolved Segment of Neoliberalism Perspective: Endeavors and Challenges - Korbaffo, Yosef Serano; Kalembang, Elpius; Nurak, Ronaldus (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2024)
This article discusses the resolution of the land border dispute between Indonesia and Timor Leste at Bidjaele Sunan-Oben and Noelbesi-Citrana, two points that are classified as unresolved segments. Border negotiations between the two countries have been going on since 2000 and only two remain, namely Bidjaele Sunan-Oben and Noelbesi-Citrana, due to the different perceptions of the two countries at these points. In 2019, a final agreement regarding the two points was reached and outlined in the Agreed Principles on The Final Settlement 2019. This research uses a qualitative method with a case study approach. Using the theory of neoliberalism, this article finds that the cooperation between Indonesia and Timor Leste through the mediation of international regimes has proven effective in resolving land border disputes at the two points in question. However, the Covid-19 epidemic and Timor Leste's absence from demarcation activities continue to obstruct the two countries' technical settlement. Keywords: Neoliberalism, International Regime, Land Boundary Disputes, Unresolved Segment, Indonesia-Timor Leste Artikel ini mendiskusikan penyelesaian sengketa batas darat Indonesia dan Timor Leste di Bidjaele Sunan-Oben dan Noelbesi-Citrana, dua titik yang tergolong unresolved segment. Perundingan batas kedua negara Leste telah dimulai sejak tahun 2000 hingga saat ini. Proses tersebut menyisahkan 2 titik tersisa yakni Bidjaele Sunan-Oben dan Noelbesi-Citrana akibat adanya perbedaan persepsi kedua negara pada titik dimaksud. Pada tahun 2019, kesepakatan final terkait kedua titik tersebut berhasil dicapai dan dituangkan dalam Agreed Principles on The Final Settlement 2019. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Dengan menggunakan teori neoliberalisme, artikel ini menemukan bahwa kerjasama Indonesia dan Timor Leste melalui perantaraan rezim internasional terbukti ampuh dalam menyelesaikan sengketa batas darat pada kedua titik dimaksud. Namun Pandemi Covid-19 dan ketidakhadiran Timor Leste dalam kegiatan demarkasi masih menjadi penghambat penyelesaian teknis kedua negara. Kata-kata kunci: Neoliberalisme, Rezim Internasional, Sengketa Batas Darat, Unresolved Segment, Indonesia-Timor Leste